CDK4/6 inhibitors improve the anti-tumor efficacy of lenvatinib in hepatocarcinoma cells - Digiacomo, Graziana; Fumarola, Claudia; La Monica, Silvia; Bonelli, Mara; Cavazzoni, Andrea; Galetti, Maricla; Terenziani, Rita; Eltayeb, Kamal; Volta, Francesco; Zoppi, Silvia; Bertolini, Patrizia; Missale, Gabriele; et al. (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is the most frequent primary liver cancer with a poor prognosis and limited treatment options. Considering that alterations of the CDK4/6-cyclin D-Rb pathway occur frequently in HCC, we tested the efficacy of two CDK4/6 inhibitors, abemaciclib and ribociclib, in combination with lenvatinib, a multi-kinase inhibitor approved as first-line therapy for advanced HCC, in a panel of HCC Rb-expressing cell lines. The simultaneous drug combinations showed a superior anti-proliferative activity as compared with single agents or sequential schedules of treatment, either in short or in long-term experiments. In addition, the simultaneous combination of abemaciclib with lenvatinib reduced 3D cell growth, and impaired colony formation and cell migration. Mechanistically, these growth-inhibitory effects were associated with a stronger down-regulation of c-myc protein expression. Depending on the HCC cell model, reduced activation of MAPK, mTORC1/p70S6K or src/FAK signaling was also observed. Abemaciclib combined with lenvatinib arrested the cells in the G1 cell cycle phase, induced p21 accumulation, and promoted a stronger increase of cellular senescence, associated with elevation of β-galactosidase activity and accumulation of ROS, as compared with single treatments. After drug withdrawal, the capacity of forming colonies was significantly impaired, suggesting that the anti-tumor efficacy of abemaciclib and lenvatinib combination was persistent. Our pre-clinical results demonstrate the effectiveness of the simultaneous combination of CDK4/6 inhibitors with lenvatinib in HCC cell models, suggesting that this combination may be worthy of further investigation as a therapeutic approach for the treatment of advanced HCC.